Conceptual review of key themes in treating prostate cancer in older adults. Issue 5 (June 2020) - Sedhom, Ramy; Gupta, Arjun
Highlights: Treatment of localized prostate cancer for older men who are not likely to benefit is a low-value health care service. Individualized treatment plans should weigh remaining life expectancy, comorbidities, the likelihood of disease progression, treatment preferences, and potential adverse effects. Any therapy, including seemingly benign interventions such as androgen deprivation therapy carry a major risk of adverse events, especially in frail older adults. Bone-modifying agents are not approved for reducing risk of, or time to skeletal-related events in patients with castrate-sensitive prostate cancer, or in patients with non-bone metastatic castrate-resistant prostate cancer. In older adults, treatment decisions are more complex because of the scarcity of data from large randomized studies and the heterogeneity of this population with regards to different geriatric domains.